MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS X.3 SMAN 1 HARUAI PADA MATERI LISTRIK DINAMIS MELALUI MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT - Sudiyono Sudiyono (Universitas Lambung Mangkurat, 2012)
Implementation of Team Games Tournament (TGT) on Dynamic Electric System learning was investigated. This study aims to improve student learning outcomes and students' motivation towards implementation of TGT learning model. This study used action research design with two cycles. Each cycle consists of planning, acting, observing and reflecting phase. Research subjects were 15 students of X3 grade SMA Negeri 1 Haruai on academic year of 2011/2012. Data were collected through test, questionnaire, and observation and analyzed qualitatively. The results showed that implementation of TGT in Dynamic Electric System learning increased the student’s learning outcomes, meanwhile, students' motivation was good category.Key words: Team Games Tournament, dynamic electricity, motivation.